HUBUNGAN KECERDASAN EMOSIONAL DENGAN RAIHAN PRESTASI ATLET WANITA - Nur Andini Suryalestari, - (2022)
This study aims to find out the relationship between emotional intelligence and achievement of female shooting athletes, in addition, in this study wanted to find out if there are the most significant components of intelligence that are related to women. The research methods used in this study are descriptively quantitative with a correlation approach. Data collection is used using instruments such as EIS or Emotional Intellegence Scale cookies. The samples in this study used female shooting athletes who had participated in the National Sports Week (PON) XX Papua. The sample numbered 8 people with sampling techniques using purposive sampling. The results showed that there are 4 components of emotional intelligence that have significant relationships and 2 components that do not have relationships. Components that have a relationship with achievement include self-awareness, self-regulation, motivation and acceptance of emotions, while the other 2 components, empathy and social skills do not have a significant relationship with the achievements of female shooting athletes.